Distribution and Expression of Vimentin and Desmin in Broiler Pectoralis major Affected by the Growth-Related Muscular Abnormalities - Soglia, Francesca; Mazzoni, Maurizio; Zappaterra, Martina; Di Nunzio, Mattia; Babini, Elena; Bordini, Martina; Sirri, Federico; Clavenzani, Paolo; Davoli, Roberta; Petracci, Massimiliano (Frontiers in Physiology, 2020)
Desmin (DES) and Vimentin (VIM) exert an essential role in maintaining muscle cytoarchitecture and since are considered reliable markers for muscle regeneration, their expression has been extensively investigated in dystrophic muscles. Thus, exhibiting features similar to those of human dystrophic muscles, the present study aimed at assessing the distribution of VIM and DES proteins and the expression of the corresponding genes in Pectoralis major muscles affected by white striping (WS), wooden breast (WB) and spaghetti meat (SM) abnormalities as well as in those having macroscopically normal appearance (NORM). For this purpose, 20 Pectoralis major muscles (5/group) were collected from the same flock of fast-growing broilers to perform immunohistochemistry, immunoblotting and gene expression. Immunohistochemical analyses showed an increased number of fibers immunoreactive to both VIM and DES in WS and WB, while only a few immunoreactive fibers were observed in NORM. Concerning the protein level, if compared with NORM, a 55% increase in VIM content was found in WB affected cases (P < 0.05) thus suggesting the development of intense regenerative processes in an early-stage within these muscles. The significantly higher amount of DES (+53) found in WS might be attributed to a progression of the regenerative processes that require its synthesis to preserve the structural organization of the developing fibers. On the other hand, significantly lower VIM and DES contents were found in SM. About gene expression, VIM mRNA levels gradually increased from the NORM to the SM group, with significantly higher gene expressions in WB and SM samples compared to the NORM group (P = 0.009 for WB vs. NORM and P = 0.004 for SM vs. NORM). Similarly, the expression of DES gene showed an increase from the NORM to WB group (P = 0.05). Overall, the findings of the present study suggest that intense regenerative processes take place in both WB and WS muscles although a different progression of regeneration might be hypothesized. On the other hand, the lack of correspondence between VIM gene expression and its protein product observed in SM suggests that VIM may also exert a role in the development of the SM phenotype.